Word or morpheme? Investigating the representation units of L1 and L2 Chinese compound words in mental lexicon using a repetition priming paradigm. Issue 7 (9th August 2022) - Gao, Fei; Wang, Jianqin; Zhao, Cecilia Guanfang; Yuan, Zhen
ABSTRACT: The present study used a repetition priming paradigm to investigate the basic morphological units stored in mental lexicon for Chinese as second language learners (L2) and Chinese native speakers (L1). Meanwhile, the modulation of Chinese morpheme property (bound or free) in lexical processing was examined. The results revealed that for intermediate-level L2 learners, Chinese words could be accessed through either whole-words or morphemes, while advanced-level learners and Chinese natives might employ a whole-word pathway. This might suggest that as language proficiency and reading experience develops, learners tend to rely more on whole-words as a processing strategy. Regarding the morpheme property effect, bound morphemes reported a greater priming effect than free morphemes in lexical decision tasks for both L1 and L2 speakers, which was interpreted with an interactive-activation framework.